Virtual Ethnography of Ethical Behavior Communicating Netizens on Infrastructure Development Issues on the Instagram Account of the Governor of North Sumatra @Edy_Rahmayadi - Ismail, Fauzan; Pohan, Syafruddin; Ginting, Rahmanita (Formosa Journal of Science and Technology, 2023)
This study aims to analyze the ethical communication behavior of netizens on infrastructure development issues on the Instagram account @edy_rahmayadi interpretively and to analyze the constructed motives in the netizens' interaction space on @edy_rahmayadi's Instagram posts, especially on infrastructure development issues in North Sumatra, in shaping public sentiment towards Edy Rahmayadi as the Governor of North Sumatra. The research methodology used in this study is a qualitative approach with a virtual ethnography method through data collection techniques such as participant observation, interviews, documentation collection, and triangulation. Data analysis uses the interactive model of Miles, Huberman, and Saldana. The results showed that the ethical communication behavior of netizens on @edy_rahmayadi's Instagram account was formed by several motives, including social background (age, religion, ethnicity, race, etc.), political interests that are still influenced by the 2018 North Sumatra gubernatorial election and Edy Rahmayadi's current political stance, professional and group interests, and other aspects related to current conditions in the field.